CONTROL OF JUVENILE DELINQUENCY THROUGH COUNSELING SERVICES GROUP IN STATE SMP NEGERI 8 PADANGSIDIMPUAN ACADEMIC YEAR 2015-2016 - Malim Soleh Rambe (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The study is based on the problem of juvenile delinquency levels are still students in the school environment, and the general problem of this research is